The MCG Medical Teacher's Handbook - Christopher White; Kathy Davies; Janis Work; Andrew Albritton; Clare Billman; Ruth Fincher; Ralph Gillies; Valera Hudson; Carolyn Murdoch; Carol Nichols; Sylvia Smith; Andria Thomas; et al. (Association of American Medical Colleges, 2009)
Abstract Introduction Medical school educators typically have extensive knowledge in the area of their professional discipline, but little or no formal training in educational theory or techniques. Their demanding clinical, teaching, and/or research responsibilities leave them little time for improving their own educational skills by attending scheduled courses or workshops. This short handbook was written to provide brief, practical, useful information on teaching, learning, evaluation, and career development for medical school faculty who have interest, but a limited background, in formal educational theory and methodology. Methods This handbook is also intended to be a resource on educational theory and principles that educators may consult at their leisure. The handbook is composed of five chapters, each containing sections that are formatted as follows: introduction, background, discussion, and pearls to remember. Chapter 1 provides general background on learning theories and implications for teaching. Chapter 2 discusses specific teaching techniques, such as giving a lecture with impact and using PowerPoint effectively. Chapter 3 deals with other aspects of teaching, such as tips on incorporating cultural competency issues and how to deal with problem learners. Chapter 4 discusses curriculum issues, such as how to write objectives and construct good examination items. Chapter 5 focuses on career development, including promotion and tenure, building an educator's portfolio, and planning and conducting educational research. Each section is freestanding and concise? a few key references are listed at the end for readers who want to explore the topic further. Results Most of the material in the handbook has been used in faculty development workshops for Medical College of Georgia faculty. Informal feedback from faculty has been very positive. Discussion The handbook is targeted primarily for those who teach medical students. It should be especially helpful to faculty who are beginning their teaching careers, and those who are assuming more of a research or leadership role in medical education.